Об обособлении нового для науки подсемейства Euryteinae subfam. n. (Crustacea, Copepoda) - Монченко, В.И. (Вестник зоологии, 1975)
The morpho-taxonomic analysis is presented for the genus Euryte Philippi. There is a number of sufficient morphological structures absent in other representatives of the family Cyclopidae for separation this genus in the new subfamilyThe diagnosis of Euryteinae Monchenko subfam. nov.: 21 (seldom 20)-segmented antennulae, maxillar palp is presented by a masticatory plate with 5-6 distal dents. and 4 lateral setae; maxillipeds of prehensile type, bent, with 4-5 setae and 2 apical hooks; most of the inner appendages on exo- and endopods of P-P, are presented by broad lanceolate spines; a sexual dimorphism in armature of Ps is absent. The only (and type) genus is Euryte Philippi.